Facile synthesis of porous Co3O4 nanoflakes as an interlayer for high performance lithium–sulfur batteries. Issue 17 (15th April 2020) - Zheng, Xiao-Xiao; Zhao, Shi-Xi; Yang, Jin-Lin; Lu, Yi-Ming; Wu, Qi-Long; Zeng, Xiang-Tian
Abstract : Co3 O4 nanoflakes were fabricated using oil bath and calcination methods. Lithium–sulfur batteries with Co3 O4 –super P interlayer exhibited better performance attributed to the synergistic effects of Co3 O4 –super P. Abstract : The "shuttle effect" of long-chain polysulfides and the low conductivity of elemental sulfur lead to the inferior cycling stability of lithium–sulfur batteries and imped their practical applications. Herein, Co3 O4 nanoflakes with uniform macro pores distribution were synthesized via facile oil bath and calcination methods. Coupled with super P and coated on common polypropylene separators, they were expected to hinder the migration of lithium polysulfides (LiPSs) and accelerate the redox kinetics of polysulfides. Coin cells assembled with the Co3 O4 –super P interlayer exhibited a capacity of 760 mA h g −1 at 1 C, maintained 598 mA h g −1 after 350 cycles, and the decay rate of discharge capacity was only about 0.062% per cycle. Such high performance can be attributed to the synergistic effects between polar Co3 O4 and conductive super P. The facile fabrication method and high performance make the Co3 O4 -super P interlayer a feasible material to apply in lithium-sulfur batteries.